Anaerobic biodegradation of phenolic compounds in digested sludge. - Boyd, S A (1983)
We examined the anaerobic degradation of phenol and the ortho, meta, and para isomers of chlorophenol, methoxyphenol, methylphenol (cresol), and nitrophenol in anaerobic sewage sludge diluted to 10% in a mineral salts medium. Of the 12 monosubstituted phenols studied, only p-chlorophenol and o-cresol were not significantly degraded during an 8-week incubation period. The phenol compounds degraded and the time required for complete substrate disappearance (in weeks) were: phenol (2), o-chlorophenol (3), m-chlorophenol (7), o-methoxyphenol (2), m- and p-methoxyphenol (1), m-cresol (7), p-cresol (3), and o-, m-, and p-nitrophenol (1). Complete mineralization of phenol, o-chlorophenol, m-cresol, p-cresol, o-nitrophenol, p-nitrophenol, and o-, m-, and p-methoxyphenol was observed. In general, the presence of Cl and NO2 groups on phenols inhibited methane production. Elimination or transformation of these substituents was accompanied by increased methane production, o-Chlorophenol was metabolized to phenol, which indicated that dechlorination was the initial degradation step. The methoxyphenols were transformed to the corresponding dihydroxybenzene compounds, which were subsequently mineralized.